ANALYSIS OF THE EXPECTED EFFECTS OF ADOPTING THE APPLICATION OF THE FINANCIAL REPORTING STANDARD IFRS 18 (PRESENTATION AND DISCLOSURE) ON THE QUALITY OF ACCOUNTING INFORMATION IN BANKS - Lecturer Dr. Saja Akram Abdulrazzaq AlShaikhli (Scholars Digest Publishing, 2025)
This research focuses on an important topic: the adoption of IFRS 18 (Presentation and Disclosure) for financial statements, the implications of its implementation in the banking sector, and its relationship to the quality of accounting information. This standard will replace International Accounting Standard IAS 1 (Presentation of Financial Statements). IFRS 18 Presentation and Disclosure will be the result of requirements raised by investors and other stakeholders who need important information for decision-making purposes. This standard seeks to provide clearer and more accurate foundations for stakeholders by standardizing financial statements and, consequently, the resulting information, so that it reaches all stakeholders in the same form through standardized presentation and disclosure. Although this standard replaces IAS 1, many of the requirements of IAS 1 have been transferred to IFRS 18. The research reached a number of conclusions, the most important of which is that the implementation of IFRS 18 meets the needs of many stakeholders, primarily investors, as it answers their inquiries through the quality of information that can be provided. Obtaining it as a result of unifying data presentation, and the most important recommendations are that economic units should work on preparing and taking all accounting and technical measures to meet the requirements of this standard.
Keywords: IFRS 18, presentation and disclosure, quality of accounting information, transparency, reliability, negative and positive effects.